2010
DOI: 10.1103/physrevlett.104.220405
|View full text |Cite
|
Sign up to set email alerts
|

Zero-Transmission Law for Multiport Beam Splitters

Abstract: The Hong-Ou-Mandel effect is generalized to a configuration of n bosons prepared in the n input ports of a Bell multiport beam splitter. We derive a strict suppression law for most possible output events, consistent with a generic bosonic behavior after suitable coarse graining.PACS numbers: 03.67. Lx, 05.30.Jp, The Hong-Ou-Mandel (HOM) effect [1] is an impressive manifestation of the bosonic quantum nature of photons. In the original experiment, two identical photons are sent simultaneously (within their cohe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
188
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 123 publications
(194 citation statements)
references
References 23 publications
6
188
0
Order By: Relevance
“…The theoretical prediction fits the experimental data perfectly well, without adjustable parameters besides the overall count rate. Note that bunching signals, as the (4, 0) event observed here, always exhibit a monotonic transition, as a consequence of the bosonic enhancement (28) of the associated, unique many-particle path, which induces the strict hierarchy p Table 1. We stress that the encountered nonmonotonicity in the (2, 2) event is fundamentally distinct from oscillating signals originating from singlephoton interference in refs.…”
mentioning
confidence: 99%
“…The theoretical prediction fits the experimental data perfectly well, without adjustable parameters besides the overall count rate. Note that bunching signals, as the (4, 0) event observed here, always exhibit a monotonic transition, as a consequence of the bosonic enhancement (28) of the associated, unique many-particle path, which induces the strict hierarchy p Table 1. We stress that the encountered nonmonotonicity in the (2, 2) event is fundamentally distinct from oscillating signals originating from singlephoton interference in refs.…”
mentioning
confidence: 99%
“…, respectively, see (151), as a function of the backscattering angle θ. Negative and positive θ correspond to an optical thickness of b = 25 and b = 5, respectively.…”
Section: Integral Equation For the Average Densitymentioning
confidence: 99%
“…In total, we get the same result as if the particles were distinguishable. This equivalence is generally valid if all particles are prepared in the same initial state, and if the Hamiltonian is symmetric under exchange of particles [151].…”
mentioning
confidence: 99%
“…The simplest case is the Hong-Ou-Mandel (HOM) effect when two particles impinge on distinct ports of a balanced beam splitter: quantum interference suppresses the coincident output (one particle per each output) in the case of bosons and the single-port output (both particles in either output) in case of fermions. In the multi-particle case, a sort of generalised HOM effect occurs for symmetric multiport beam splitters [5][6][7][8]. In particular, Tichy et al [7] showed that for a particular class of multiports, namely Bell or Fourier multiports, and input states with cyclic symmetry, a full suppression of most of the output combinations is observed; a * andrea.crespi@polimi.it simple analytical law gives a sufficient criterion for such suppression.…”
Section: Introductionmentioning
confidence: 99%
“…It has to be noted that the existence of a sharp suppression law directly comes from the symmetry characteristics of the matrix. While it has been conjectured that other suppression laws could exist for other class of symmetric unitaries, only the class of Fourier matrices has been investigated extensively up to now [7,20,21].…”
Section: Introductionmentioning
confidence: 99%